NO2 and SO2 Exposure to Gas Station Workers Health Risk in Kendari City - Alchamdani Alchamdani (Universitas Airlangga, 2019)
Gas station workers played an important role in providing fuel needs in the community for the transportation system to run smoothly. The higher motor vehicle user, the intensity of refueling also increases. They were at high risk of being exposed to hazardous pollutants from both vehicle emissions and fuel vapors. Although NO2 and SO2 had non-carcinogenic effects, they are still irritants that cause chronic airway disorders. This study aims to analyze the health risks experienced by gas station workers due to NO2 and SO2 exposure in Kendari City. This research was a Quantitative Descriptive study with Environmental Health Risk Method Analysis. The number of samples was 13 operators chosen with total sampling. Measurement of NO2 and SO2 concentrations were carried out in the morning, afternoon and evening. The results of this study showed the highest intake value obtained for NO2 (real-time) was 0.00635 mg/kg/day and SO2 (real-time) 0.00057 mg/kg/day. The highest risk level obtained for NO2 is 0,31775 (RQ<1) and SO2 0,00275 (RQ<1). The conclusion of this study is the quality of ambient air NO2 and SO2 at SPBU 74,931.10 is still safe and meets the National Ambient Air Quality Standard in a short time. But otherwise, it will be at high risk for health if the operator was exposed for a long time and continuously. It should be made an effort to monitor and control air pollution. As well as the policy of using Personal Protective Equipment to minimizing exposure to ambient pollutants.